Would right atrial stretch inhibit sodium intake following GABAA receptor activation in the lateral parabrachial nucleus? - Shimoura, Caroline Gusson [UNESP] (2013)
The knowledge of the mechanisms underlying circulating volume control may be achieved by stretching a balloon placed at the junction of the superior vena cava-right atrial junction (SVC-RAJ). We investigated whether the inflation of a balloon at the SVC-RAJ inhibits the intake of 0.3M NaCl induced by GABAA receptor activation in the lateral parabrachial nucleus (LPBN) in euhydrated and satiated rats. Male Wistar rats (280-300g) with bilateral stainless steel LPBN cannulae and balloons implanted at the SVC-RAJ were used. Bilateral injections of the GABAA receptor agonist muscimol (0.5ηmol/0.2l) in the LPBN with deflated balloons increased intake of 0.3M NaCl (30.1±3.9 vs. saline: 2.2±0.7)ml/210min, n=8) and water (17.7±1.9 vs. saline: 2.9±0.5ml/210min). Conversely, 0.3M NaCl (27.8±2.1ml/210min) and water (22.8±2.3ml/210min) intake were not affected in rats with inflated balloons at the SVC-RAJ. The results show that sodium and water intake induced by muscimol injected into the LPBN was not affected by balloon inflation at the SVC-RAJ. We suggest that the blockade of LPBN neuronal activity with muscimol injections impairs inhibitory mechanisms activated by signals from cardiopulmonary volume receptors determined by balloon inflation. © 2013 The Authors.